Copper doped manganese dioxide as counter electrode for dye-sensitized solar cells - Belqasem Aljafari; Subbiah Vijaya; Arash Takshi; Sambandam Anandan (Arabian Journal of Chemistry, 2022)
Many materials have been tried as the counter electrode (CE) material as a substitute to the noble metal Pt in dye-sensitized solar cells (DSSCs). The CE property is critical to the operation of a DSSC as it catalyzes the reduction of I3- ions and retrieves the electrons from the photoanode. Here we have explored the application of manganese dioxide (MnO2) and copper-doped manganese dioxide (Cu-MnO2) nanoparticles as CE candidates for DSSCs mainly as low-cost alternatives to Pt. A simple hydrothermal method was followed to synthesize α-MnO2 and Cu-MnO2 nanoparticles at a temperature of 140 °C for 14 h. The nanoparticles were characterized to prove its electrocatalytic abilities for DSSCs. DSSC devices fabricated with 10 wt% Cu-MnO2 as CE showed the best VOC of 781 mV, ISC of 3.69 mA/cm2, FF of 0.50, and %PCE of 1.7 whereas Pt as CE showed VOC of 780 mV, ISC of 14.8 mA/cm2, FF of 0.43, and %PCE of 5.83 under 0.85 Sun. The low-cost feature of using Cu-MnO2 is encouraging to further study the factors that can improve the efficiency of DSSCs with alternative CEs to conventional Pt electrodes.